"Keep it safe" : minimizing alcohol-related harm through street interventions - Jervis, Ros, (SAGE knowledge. Cases., 2016)
Wolverhampton City Primary Care Trust (PCT) is a legal organisation that launched a programme ("Keep it Safe") designed to solve issues emanating from alcohol abuse. In cooperation with multiple partners, the PCT had a number of goals for its new programme, including youth consultation, prevention of assault and violence, and domestic abuse. Following a number of campaigns and strategies to promote its mission, PCT marketers present us with the leading data they compiled from their thorough research using the marketing mix (the 4Ps: product, promotion, place, and price), and ultimately evaluate the effectiveness of their programme.